2016
DOI: 10.1103/physreve.94.032125
|View full text |Cite
|
Sign up to set email alerts
|

Flat phase of quantum polymerized membranes

Abstract: We investigate the flat phase of quantum polymerized phantom membranes by means of a nonperturbative renormalization group approach. We first implement this formalism for general quantum polymerized membranes and derive the flow equations that encompass both quantum and thermal fluctuations. We then deduce and analyze the flow equations relevant to study the flat phase and discuss their salient features: quantum to classical crossover and, in each of these regimes, strong to weak coupling crossover. We finally… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 103 publications
(290 reference statements)
7
33
0
Order By: Relevance
“…Our results suggest, in agreement with Ref. [11] that quantum fluctuations leave the membrane flat on the large scale. The interesting logarithmic corrections implied by D = 2 being the upper critical dimension of quantum membranes [11] cannot be addressed here because of computational limitations.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Our results suggest, in agreement with Ref. [11] that quantum fluctuations leave the membrane flat on the large scale. The interesting logarithmic corrections implied by D = 2 being the upper critical dimension of quantum membranes [11] cannot be addressed here because of computational limitations.…”
supporting
confidence: 93%
“…In anticipation of increasing system size along the Trotter dimension, we start with a smaller membrane of N = 19 440 atoms and proceed by cooling it down. Figure 2 shows the PIMC height correlation function for N = 19 440 (220Å linear size) at T = 300, 50 and 12.5 K. Both T = 50 and 12.5 K data show a clear crossover from classical correlations for q < q T to quantum ones taking place, again in agreement with predictions, for q > q T , where [11,27] q T = ρ κ…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Recently however, following previous works on disorder-free polymerized membranes [50,52,55,[59][60][61] the present authors [3] have performed a NPRG approach of the model considered within a perturbative framework by Morse et al [57,58] and whose action is given by:…”
Section: Nprg Analysismentioning
confidence: 99%
“…We would like to reinforce that even neglecting out-of-plane vibrational modes, our results for the flat membrane are a good reference for first estimates because they resemble the physics of a free-standing graphene monolayer in agreement with experiments. Very recently, PIMC simulation results [48] in agreement with [49] have shown that the crossover between classical and quantum contribution for the out-of-plane vibrational modes should occur around 50K. For lower temperatures quantum fluctuations should leave the membrane flat on the large scale.…”
Section: Numerical Results and Discussionmentioning
confidence: 52%